Makna Al-Lamam Perspektif Wahbah Az-Zuhaili dalam Tafsir Al-Munir - Harahap, Maria Ulfa (ANWARUL, 2023)
The meaning of al-Lamam in the Koran is minor sins or minor mistakes that refer to strong feelings of guilt and remorse for mistakes or sins that have been committed, with the urge to improve oneself and repent. The background of the problem of this thesis is how the meaning of the word al-Lamam according to wahbah az-Zuhaili, from this background, the aim of the research arises, namely, to find out what the meaning of the word al-Lamam is in al-munir's interpretation. This study is a qualitative research and the interpretation taken is the interpretation of al-Munir's work by Wahbah az-Zuhaili. In this discussion, it focuses on the meaning of al-lamam itself and also a comparison of the meaning of the word al-Lamam from the interpretations of al-munir, ibn katsir and other interpretations. But the main focus is al-Munir's interpretation.